The Chiefdom of Cubiga: Ethnohistory and Archaeology in Central Caribbean Panamá - Brizuela, Álvaro M. (2019)
A literature review of ethnohistoric sources and a new chronology derived from 85 radiometric dates are presented for Central Caribbean Panamá as partial results of the Proyecto de Monitoreo y Rescate Arqueológico Cobre Panamá (located in Donoso, Colón). The Cubiga chiefdom (subordinate to Veragua) is identified as corresponding to the study area. The majority of dates correspond to a Late Ceramic period, previous to the first European Contact (AD 1200-1500). It is noted that the homogeneus distribution of archaeological sites coincides with the ethnohistorical descriptions.